Evaluation of the Water Quality and Distribution of Heavy Metals in the Gomti River Flowing Through the Urban Region of Lucknow, India - Gondial, Neha; Bharti, Sandhya (UI Scholars Hub, 2024)
The physicochemical properties and heavy metals contents of the Gomti River water (GRW) samples collected from five selected sites covering a stretch of 31 km in Lucknow, Uttar Pradesh, India were ascertained. The sites were Ghaila Pul, Mehndi Ghat, Shaheed Smarak, Kukrail Junction, and Bande Dam, represented as S1, S2, S3, S4, and S5, respectively, following from upstream to downstream. S1 was considered as a reference site. The values of pH, temperature, total dissolved solids (TDS), electrical conductivity (EC), turbidity, dissolved oxygen (DO), biochemical oxygen demand (BOD), total hardness (TH), total chloride (TC), total alkalinity (TA), total acidity (TAC), total free CO2, total NO3, and NO2 differed with sites. The Fe, Co, Ni, Cu, Al, Zn, As, Mo, Cd, Cr, and Pb levels were also investigated. Except for Zn and Cu, all other metals were detected beyond the levels allowed by the BIS (2012) and Organization of Economic Corporation and Development (OECD, 2020) for water bodies. Further, the current finding suggests that the discharge of untreated industrial, agricultural, and domestic effluents into the Gomti River is unendurable.